Achalasia following reflux disease: coincidence, consequence, or accommodation? An experience-based literature review - Vereczkei A; Bognár L; Papp A; Horváth ÖP (Dove Medical Press, 2017)
András Vereczkei, Laura Bognár, András Papp, Örs Péter Horváth Department of Surgery, University of Pécs, Pécs, Hungary Abstract: Achalasia is a motility disorder of the esophagus characterized by the defective peristaltic activity of the esophageal body and impaired relaxation of the lower esophageal sphincter due to the degeneration of the inhibitory neurons in the myenteric plexus of the esophageal wall. The histopathological and pathophysiological changes in achalasia have been well described. However, the exact etiological factors leading to the disease still remain unclear. Currently, achalasia is believed to be a multifactorial disease, involving both extrinsic and intrinsic factors. Based on our experience and the review of literature, we believe that gastroesophageal reflux disease (GERD) might be one of the triggering factors leading to the development of achalasia. However, it is also stated that the two diseases can simultaneously appear independently from each other. Considering the large number and routine treatment of patients with GERD and achalasia, the rare combination of the two may even remain unnoticed; thus, the analysis of larger patient groups with this entity is not feasible. In this context, we report four cases where long-standing reflux symptoms preceded the development of achalasia. A literature review of the available data is also given. We hypothesize that achalasia following the chronic acid exposure of the esophagus is not accidental but either a consequence of a chronic inflammation or a protective reaction of the organism in order to prevent aspiration and lessen reflux-related symptoms. This hypothesis awaits further clinical confirmation. Keywords: achalasia, gastroesophageal reflux disease, Barrett’s esophagus, Nissen fundoplication